Evaluation of Moraine Sediment Dam Stability Under Permafrost Thawing in Glacial Environments: A Case Study of Gurudongmar Lake, Sikkim Himalayas - Anil Kumar Misra; Amit Srivastava; Kuldeep Dutta; Soumya Shukla; Rakesh Kumar Ranjan; Nishchal Wanjari (Applied Sciences)
This study assesses the risks of glacial lake outburst floods (GLOFs) from moraine sediment dams around Gurudongmar Lake in the Northern Sikkim Himalayas at an elevation of 17,800 feet. It focuses on three moraine sediment dams, analysing the implications of slope failure on the upstream side and the downstream stability under steady seepage conditions, as well as the risks posed by permafrost thawing. Using a comprehensive methodology that includes geotechnical evaluations, remote sensing, and digital elevation models (DEMs), the research employs finite element analysis via PLAXIS2D for the stability assessment. The main findings indicate a stratification of sediment types: the upper layers are loose silty sand, while the lower layers are dense silty sand, with significant variations in shear strength, permeability, and other geotechnical properties. Observations of solifluctions suggest that current permafrost conditions enhance the dams’ stability and reduce seepage. However, temperature trends show a warming climate, with the average days below 0 °C decreasing from 314 (2004–2013) to 305 (2014–2023), indicating potential permafrost thawing. This thawing could increase seepage and destabilise the dams, raising the risk of GLOFs. Numerical simulations reveal that scenarios involving water level rises of 5 and 10 m could lead to significant deformation and reduced safety factors on both the upstream lateral dams and downstream front dams. The study emphasises the urgent need for ongoing monitoring and risk assessment to address the potential hazards associated with GLOFs.